Pre-Columbian jadeitite artifacts from San Salvador Island, Bahamas and comparison with jades of the eastern Caribbean and jadeitites of the greater Caribbean region. (August 2019) - Harlow, George E.; Berman, Mary Jane; Cárdenas Párraga, Juan; Hertwig, Andreas; García-Casco, Antonio; Gnivecki, Perry L.
Abstract: Four artifacts from San Salvador Island, Bahamas, with affinities to jadeite jade were studied by mineralogical and petrographical techniques and compared to similar studies of jadeite rock (jadeitite) from sources in the greater Caribbean region: Guatemala (both north and south Motagua mélange occurrences); the Sierra del Convento Mélange, Cuba; and the Río San Juan Complex, Dominican Republic. Three of the four artifacts are jadeite jade. The fourth is a metavolcanic rock of greenschist facies metamorphism. Each of the three jadeitite objects is distinct in terms of mineral assemblage and microscopic minerals intergrowth textures. One artifact manifests strong similarities with a variety of jadeitite known from Cuba, the closest source geographically to the Bahamas. The other two artifacts display unique characteristics of either mineral assemblage or texture that have not been observed to date in rocks from the known sources. Consequently, search must continue for greater diversity within the documented sources or new sources of jadeite jade that conform to what was observed must be found. Highlights: Three greenstone objects from two Lucayan sites located on San Salvador, Bahamas, were identified as jadeitite. One jadeitite artifact was sourced to the Sierra del Convento Mélange in Cuba. The Río San Juan Complex, Dominican Republic and the North Motagua Mélange, Guatemala contain similar source material. Petrological, mineralogical, and geochemical analyses are critical to lithic sourcing of jadeitite artifacts.